THE INFLUENCE OF WORK-LIFE BALANCE ON TURNOVER INTENTION MEDIATED BY JOB SATISFACTION OF EMPLOYEES AT PT. PERMODALAN NASIONAL MADANI IN PEKANBARU BRANCH - Purnama, Andhini; Pratikno, Yuni; Jati, Prihatina (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2025)
This study aims to analyze the effect of Work-life Balance on Turnover Intention with Job Satisfaction as a mediating variable among employees of PT Permodalan Nasional Madani (PNM) Pekanbaru Branch. The research method employed regression and path analysis using SPSS version 29. The results indicate that Work-life Balance has a negative and significant effect on Turnover Intention (-0.805; p < 0.05) and a positive and significant effect on Job Satisfaction (0.454; p < 0.05). However, Job Satisfaction does not significantly affect Turnover Intention (0.079; p > 0.05). The indirect effect of Work-life Balance on Turnover Intention through Job Satisfaction is weak (0.063). The study concludes that Work-life Balance plays a crucial role in reducing employees' Turnover Intention, whereas Job Satisfaction is not a dominant factor in employees' decisions to leave the company.